260 CHANGING PATTERNS OF COLORECTAL CANCER INCIDENCE IN DISTINCT ETHNIC GROUPS IN NEW MEXICO BETWEEN 1973 AND 2001. (1st January 2005) - Struttmann, M.; Wiggins, C.; Ma, T.
Abstract : Purpose: New Mexico's (NM) tricultural population has a unique mix, consisting of 45% non-Hispanic Whites (NHW), 42% Hispanics, and 10% American Indians (AI). NM has the largest Hispanic population per capita in the United States and one of the largest AI populations. This unique population mix provides a rare opportunity to study the incidence pattern in three distinct ethnic groups in the same region over time. Recent studies have indicated a change in CRC incidence pattern in the US. The purpose of this study was to examine the possible change in CRC incidence trends in 3 major ethnic groups in NM using the Surveillance, Epidemiology, and End Results (SEER) database. Methods: Access data from the NM Tumor Registry, which is one of the 11 registries in the SEER database. From this data, we analyzed temporal changes and incidence rates per 100, 000 person-years based on ethnicity and age. Results: 1) CRC incidence in NM increased between 1973 and 1986, then decreased from 1986 to 2001. 2) When subdivided into the three ethnic groups, the incidence of CRC in NHW also increased between 1973 and 1986, and then decreased between 1986 and 2001. In contrast, CRC incidence progressively increased throughout the entire study period for Hispanics. AI had a similar incidence pattern as the Hispanics. 3) In all 3 ethnic groups, there was an age-related increase in CRC incidence (with every decade increase in age, there was a doubling of incidence of CRC). 4) Interestingly, when subdivided into ethnic and age groups, there was no age-dependent change in incidence pattern in the younger age groups (≤70). However, in the older age groups (>70), there was a decrease in CRC incidence between 1986 and 2001 in NHW, while an increase in incidence was present in Hispanics. Conclusion: The incidence of CRC in NM increased from 1973 to 1986 and then decreased between 1986 and 2001. This trend was mirrored by the NHW. In contrast, the CRC incidence in Hispanics continued to increase between 1986 and 2001. The reason for this discrepancy between the ethnic groups is unclear and requires further investigation.